‘Men zou Virgilius zien opgaen in zijn’ tolck’. De functie van Vergilius in het artistiek ondernemerschap van Joost van den Vondel - Reinders, Sophie; Blom, Frans R.E. (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2012)
This article analyzes Joost van den Vondel’s career strategies and shows that the ambition for obtaining patronage as a poet played a crucial role in the dedications of his consecutive Vergil translations. In the period 1646-1660 Vondel published three Dutch translations of Vergil, one in prose, one ‘preview’ of the poetry translation, and a final translation of the complete works rendered in verse. For each of the individual dedicatees, the Prince of Orange, the son of the Amsterdam burgomaster Cornelis de Graeff, and the mighty burgomaster himself, the publications’ paratexts work to achieve a single goal by means of this work of art: obtaining structural patronage for composing an epic.